Empowerment of Handwashing Education with Videos and Songs as a Prevention for Covid-19 - Girsang, Bina Melvia; Sinulingga, Samerdanta; Ritonga, Fajar Utama (Talenta Publisher, 2020)
Currently, there are still many people who do not care about the health conditions of themselves, their families, and the environment. Unhealthy lifestyle habits that they take for granted but can have a bad impact on society. Then, the lack of public awareness and willingness of the importance of maintaining health and implementing a healthy lifestyle by getting used to washing hands with soap. The purpose of this activity is an educational action to wash hands as a measure to prevent Covid-19 infection. The method of community service activities is carried out using video media and songs followed by 20 activity participants, the majority of whom are housewives. The results obtained from this activity were changes in the habit of washing hands using soap to 100%, variations in washing hands using soap under running water were also stated by 85% of the participants, and the response of washing hands every time they touched the surface was stated by 80% of the activity participants. The habit of washing hands using soap is expected to be a behavior that is applied every day as part of the habit adaptation in the new normal period.